2004
DOI: 10.1111/j.1472-765x.2003.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pyrimidine nucleotide formation in Pseudomonas reptilivora

Abstract: Aims: To study the regulation of de novo pyrimidine biosynthesis in the pathogenic bacterium Pseudomonas reptilivora ATCC 14836. Methods and Results: The pyrimidine biosynthetic pathway enzymes were assayed in extracts of Ps. reptilivora ATCC 14836 cells and of cells from an auxotroph lacking aspartate transcarbamoylase activity. Pyrimidine biosynthetic pathway enzyme activities in ATCC 14836 were influenced by the addition of pyrimidine bases to the culture medium with orotic acid addition inducing dihydrooro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In this study pyrimidine starvation experiments have demonstrated that the pyrimidine biosynthetic enzymes can be influenced, suggesting that regulation is occurring at the transcriptional level. This finding for P. aeruginosa is supported by the basic research of West and collaborators who have reported transcriptional regulation in a number of other Pseudomonas species (West 2004a, 2004c, West 2005a, 2005b.…”
Section: Resultssupporting
confidence: 76%
“…In this study pyrimidine starvation experiments have demonstrated that the pyrimidine biosynthetic enzymes can be influenced, suggesting that regulation is occurring at the transcriptional level. This finding for P. aeruginosa is supported by the basic research of West and collaborators who have reported transcriptional regulation in a number of other Pseudomonas species (West 2004a, 2004c, West 2005a, 2005b.…”
Section: Resultssupporting
confidence: 76%
“…OMP is an exhaustively studied metabolic enzyme that includes numerous X-ray structures . Since pyrimidines are generally important for a variety of cell function and highly regulated, inhibition of the pyrimidine biosynthetic pathway tends to stimulate or up-regulate pyrimidine salvage pathways. , Thus, pyrimidine biosynthetic pathways are a common target for drug discovery. The A. nidulans pyrG89 mutant eliminates the normal function of OMP and is similar to uaZ14 , where both are recessive, loss-of-function mutations. The pyrG89 mutant has not been characterized at the DNA or the protein level.…”
Section: Resultsmentioning
confidence: 99%
“…OMP is an exhaustively studied metabolic enzyme that includes numerous X-ray structures. 60 Since pyrimidines are generally important for a variety of cell function and highly regulated, [61][62][63][64] inhibition of the pyrimidine biosynthetic pathway tends to stimulate or up-regulate pyrimidine salvage pathways. 65,66 Thus, pyrimidine biosynthetic pathways are a common target for drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of pyrimidine biosynthesis has been investigated in certain species taxonomically assigned to the Pseudomonas fluorescens chlororaphis group, including P. fluorescens, Pseudomonas mucidolens, Pseudomonas reptilivora, Pseudomonas synxantha and Pseudomonas veronii [102][103][104][105][106][107][108][109]. The regulation of pyrimidine biosynthesis in the P. fluorescens homology group species was compared by examining uracil-related metabolite repression or the influence of pyrimidine auxotroph limitation on the biosynthetic enzyme levels (Table 3).…”
Section: Pseudomonas Fluorescens Homology Groupmentioning
confidence: 99%
“…Pyrimidine biosynthesis was shown to be regulated by pyrimidines in P. reptilivora ATCC 14836 [107]. In succinate-grown ATCC 14836 cells, uracil supplementation lowered transcarbamoylase, dehydrogenase, phosphoribosyltransferase or decarboxylase activity, while orotic acid supplementation was less effective in repressing the pathway enzymes' activity relative to each one's activity in unsupplemented cells [107].…”
Section: Pseudomonas Fluorescens Homology Groupmentioning
confidence: 99%